PENGENDALIAN INTERNAL DALAM PENGHIMPUNAN DANA NASABAH DI PD.BPR BANK SALATIGA - Sarah Wahidatun Niswah; Aprina Nugrahesthy Sulistya Hapsari (ProBank, 2019)
The purpose of this study is to look at the role of the internal auditors in  dealing with risks from customer fundraising activities in  PD.BPR  Bank Salatiga  has  been  running  effectively and  efficiently. Supervision of customer fund disbursement activities is very important in preventing the risk of fraud that may occur from the employee and the customer. Supervision carried out in preventing fraud risk starts from the risk assessment made by the internal auditor so that the impvolvement of the audit in assessing risk and handling the findings that occur can be resolved and provide recommendations related parties to the risk found. The reaserch method used is a qualitative descriptive method with a phenomenological approach in PD.BPR Bank Salatiga. Risk analysis mapping will be synchronized with possible events that have occurred so that the role of the internal auditors is known in assessing and resolving the risks that accur. From the risk analysis and findings, it was found that the role of the internal auditor in assessing and resolving the risks that occurred was limited to those who handled when the problems that occurred could not be resolved by the parties concerned. Internal control carried out by the bank in assessing the risks that might occur can be said to be quite good in assessing emerging risks and overcoming the risks that arise can be resolved.